Sharia Fintech Innovation: Combining Technology and Islamic Principles in the Digital Economy - Ismail, Ozaril; Kilicy, Turkan (Journal International Economic Sharia, 2024)
Objective; This study seeks to explore the effect of technology adoption on consumer trust and experience of Sharia fintech products in Turkey, in relation to the confounding effects of regulation and culture at both the systemic and the user levels.Methods; Quantitative surveys were done together with qualitative interviews focusing on stakeholders in the Sharia fintech ecosystem. This study with a sample of 500 consumers, used descriptive and regression analysis to analyze data to test relationships of the four variables identified.Results; Show a strong and positive association between technology integration, regulation framework, consumer education, engagement in Sharia fintech products. Moreover, cultural values and user experience was central to the adoption of these financial solutions.Novelty; This paper fills the gap in the limited empirical literature towards Sharia fintech by presenting an exploratory research data on the drivers of consumer trust and engagement via real interaction, in the unique context of Turkey which has different both cultural and regulatory challenges in this regard.Research Implications; The findings present implications for Sharia fintech stakeholders to focus on technological innovations and harmonization in regulation in order to build consumer confidence and wider access of financial services for unserved communities.